Income inequality in the EU: how do member states contribute?. Issue 6 (3rd June 2014) - Papatheodorou, Christos; Pavlopoulos, Dimitris
Abstract : Purpose: – The purpose of this paper is to analyse the structure of overall inequality in the EU-15 by investigating the extent to which total inequality is attributed to inequality between or within the individual countries. Also, the paper examines whether the contribution of between-country and within-country components changed in the period between 1996 to 2008, before the outbreak of the economic crisis. Design/methodology/approach: – The paper applies a decomposition analysis by population subgroup utilizing micro-data from the ECHP and EU-SILC surveys. A number of inequality indices are employed to capture the different aspects of inequality and test the robustness of the results. Findings: – The analysis shows that the between-countries differences account only for a small part of overall inequality in the EU-15. Furthermore, the contribution of the between county component to total inequality has shrunk dramatically during the examined period. The overall EU inequality has been affected disproportionally by income disparities at the various parts of the income distribution in different countries. Practical implications: – Policies aiming to reduce inequality within each country would be far more effective in reducing overall inequality in the EU than policies targeting to reduce only disparities between member states. Originality/value: – The findings question the effectiveness of EU policy priorities to decrease inequality that have mainly focused on reducing cross-country and/or regions differences regarding certain macroeconomic indicators such as per-capita income (or GDP). The evidence suggests that the social protection system provides a useful tool in explaining the differences in inequality between countries and their contribution to overall EU inequality.